If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(a + 9) = 26 Reorder the terms: 2(9 + a) = 26 (9 * 2 + a * 2) = 26 (18 + 2a) = 26 Solving 18 + 2a = 26 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 2a = 26 + -18 Combine like terms: 18 + -18 = 0 0 + 2a = 26 + -18 2a = 26 + -18 Combine like terms: 26 + -18 = 8 2a = 8 Divide each side by '2'. a = 4 Simplifying a = 4
| p=2X | | 4x+4=3x+5 | | x+4=2x-7 | | (3u^2+2u-1)-(-6u^2+2u+2)+(6u^2+9u+2)= | | 3x-1=7-4(6-2x) | | 6(t+-2)-76=142 | | -5(r-3)-2(2r+1)=-8 | | 4(2b+3)=-3(b-1)+20 | | 36+7.1=2.5b+11.5 | | 4-5x=2x+1 | | 5x+6=3x-6 | | 16t+7=19t+2 | | x^4-8x^2+14=0 | | =300x^2-12 | | 5x+500=7x+200 | | 2x=4-3(x-2) | | 7x+200=5x+500 | | 5t-10= | | 5B+9= | | 64x^2=81 | | 5x+1/8=2 | | 3x+90-5x=60 | | n^2(-2n^2+4n-8)= | | 2y=x+10 | | 5*1.5=x | | 12-3y+y=9 | | =(2x-1)(x^2+3x-4) | | (a+3)(a+3)(a+3)= | | 0.08-0.01(x+2)=-0.03(2-x) | | c^2(c^2+4c+4)-64(c^2+4c+4)= | | -2(t-1)+8t=3t-1 | | (8b+1)(8b+1)= |